Collective vibrational modes and dielectric relaxation of Ca2ErNbO6. (November 2015) - Mukherjee, Rajesh; Dutta, Alo; Sinha, T.P.
Abstract: The double perovskite oxide calcium erbium niobate, Ca2 ErNbO6 (CEN) is synthesized by solid-state reaction technique. The Rietveld refinement of the room temperature X-ray diffraction pattern of the material shows that CEN is crystallized in the monoclinic P21 /n crystal symmetry. Vibrational properties of the sample for P21 /n symmetry are analysed using Raman and infrared spectroscopies. The dielectric relaxation and ac conductivity of CEN are investigated in the temperature range from 303 to 573 K and in the frequency range from 100 Hz to 1.1 MHz using impedance spectroscopy. Modified Cole–Cole equation is used to describe the relaxation phenomenon. The frequency dependent conductivity spectra follow the Jonscher power law. The values of Activation energy indicate that the dielectric relaxation and the conduction mechanism are due to adiabatic small polaron hopping of charge carriers. The complex impedance plane plot of the sample indicates the presence of both grain and grain-boundary effects and is analyzed by an electrical equivalent circuit consisting of resistances and constant-phase elements.